Pleomorphic adenoma of the hard palate with calcifications: an unusual presentation - Jorge Obando; Noelia Coronado; Ana Trevejo-Bocanegra (Universidad de Concepción., 2020)
Pleomorphic Adenoma (PA) is the most common benign salivary gland tumor. The most common sites for minor salivary gland from which PA arises are the palate followed by the lips and buccal mucosa. Calcifications are a common finding in major salivary glands with chronic inflammatory disorders. Major salivary gland tumors rarely show calcifications and it is less common to find them in minor salivary gland tumors. We report a case of pleomorphic adenoma of the hard palate in a 67-year-old female patient with intra-tumoral, irregular and scattered calcifications visible on computed tomography (CT). The treatment was complete surgical excision of the lesion. The diagnosis was confirmed with the histopathological study.